Pedagogical Leadership for Strengthening Collaborative Learning Ecosystems: A Systematic Literature Review of School Partnerships in Elementary Extracurricular Education - Pamujiono, Juhan; Widiyan, Agung Purwa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The growing emphasis on learner-centered education has expanded the role of school principals from administrative managers to pedagogical leaders responsible for cultivating collaborative learning ecosystems that support students’ holistic development. Within elementary education, extracurricular programs provide extended learning environments where partnerships among schools, teachers, parents, and communities contribute to meaningful educational experiences. This systematic literature review aims to synthesize current evidence on how pedagogical leadership strengthens collaborative learning ecosystems through school partnerships in the management of extracurricular education. The review adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. An initial search identified 120 studies from major academic databases, of which seven primary studies published between 2020 and 2025 satisfied the predefined inclusion criteria. The thematic synthesis revealed three major findings. First, pedagogical leadership is manifested through strategic planning, organizational coordination, monitoring, and adaptive decision-making that support sustainable extracurricular learning environments. Second, collaborative partnerships involving teachers, parents, school committees, and community stakeholders function as complementary learning resources that reinforce educational objectives beyond classroom instruction. Third, extracurricular programs are increasingly positioned as integral components of collaborative learning ecosystems that foster character development, student engagement, and competency enhancement. The review concludes that pedagogical leadership serves as the driving force in orchestrating collaborative learning ecosystems by integrating school partnerships into extracurricular education. These findings highlight the importance of strengthening leadership capacity and collaborative educational practices to enhance the quality of elementary learning environments while providing a conceptual foundation for future technology-responsive pedagogical innovations.